STABILITY OF DEFECTS AN ENTIRE CURVE OF INFINITE ORDER - Овчар, Ігор Євгенійович; Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
An entire curve of infinite order is constructed for which the values of Nevanlinnian and Valeronian defects change with linear transformation of the argument.